Investigation of automobile roads pavement deterioration trends in Lithuania - Braga, Aivaras; Puodziukas, Virgaudas; Čygas, Donatas; Laurinavičius, Alfredas (Journal of Civil Engineering and Management, 2003)
Currently there are three pavement management systems (PMS) used in Lithuania for planning and management of road maintenance and repair activities: HDM-III, HDM-4 and DAVASEMA (Lithuanian PMS). HDM pavement deterioration models are used in all of them. With the purpose of calibration and adaptation of those models in 1997 Lithuanian Pavement Deterioration Research Project was developed. The research data gathered in four years of the Project gives an opportunity to draw some conclusions on asphalt pavement deterioration in Lithuania. This article presents the main HDM asphalt pavement deterioration models, and describes the most important steps in adaptation of some input data to those models and calibration of the models to the local conditions. First Published Online: 26 Jul 2012